New model of electric traction drive based sliding mode controller in field-oriented control of induction motor fed by multilevel inverter - Chaymae Laoufi; Zouhair Sadoune; Ahmed Abbou; Mohammed Akherraz (Institute of Advanced Engineering and Science, 2020)
This paper presents a new model of electric traction drive for electric vehicle. The sliding mode speed controller applied in the Indirect Rotor Field Oriented Control is used to control the induction motor fed by the five levels Neutral Point Clamped inverter (NPC). The simulation results showed the high performances dynamics and high robustness of the proposed model, that are reflected by faster startup and good speed tracking performances in terms of response time, oscillations and disturbance rejection. Also, a comparative study between different inverter topologies: two levels inverter, three levels NPC inverter and five levels NPC inverter has been carried out. From the spectral analysis, the five-levels NPC inverter fed drive provides better dynamics of voltage and current with reduced total harmonic distortion (THD).